The TRPA1 Channel Mediates Mechanical Allodynia and Thermal Hyperalgesia in a Rat Bone Cancer Pain Model - Liu, Qiangwei; Feng, Long; Han, Xiujing; Zhang, Weidong; Zhang, Hong; Xu, Longhe (Frontiers in Pain Research, 2021)
Background: Bone cancer pain (BCP) significantly affects patient quality of life, results in great bodily and emotional pain, and creates difficulties in follow-up treatment and normal life. Transient receptor potential ankyrin 1 (TRPA1) is an essential transduction ion channel related to neuropathic and inflammatory pain. However, the role of TRPA1 in BCP remains poorly understood. This study aimed to explore the relationship between TRPA1 and BCP. Methods: A BCP model was induced by Walker256 cells to the left tibia. The sham group was induced by normal saline to the left tibia. Thereafter, pain behaviors and TRPA1 expression between the BCP group and the sham group were observed on the 14th day of modeling. The TRPA1 antagonist A967079 (10 mg/kg) was injected via tail vein. TRPA1 antisense oligodeoxynucleotide (AS-ODN, 5 nmol/10 μl) and missense oligodeoxynucleotide (MS-ODN, 5 nmol/10 μl) were intrathecally delivered via a mini-osmotic pump for 5 consecutive days to assess the effect of TRPA1 on BCP. Behavioral tests were assessed preoperatively and postoperatively. Real-time quantitative PCR and western blot analyses were used to measure TRPA1 levels among the different groups. Results: The BCP model was successfully established via X-ray and pathological sections at 14 days. Compared to the sham group, the BCP group was more sensitive to mechanical stimuli, cool stimuli and hot stimuli. Intravenously injected A967079 can relieve paw mechanical withdrawal threshold and paw withdrawal thermal latency in rats with BCP. Moreover, AS-ODN can relieve paw mechanical withdrawal threshold and paw withdrawal thermal latency in rats with BCP. Additionally, relative mRNA and protein expression of TRPA1 in the BCP group were much higher than those in the sham group (14.55 ± 1.97 vs. 1 ± 0.04, P < 0.01). Compared to the BCP group, the relative mRNA and protein expression of TRPA1 in the BCP+AS-ODN group was reduced (14.55 ± 1.97 vs. 2.59 ± 0.34, P < 0.01). Conclusions: The TRPA1 channel mediates mechanical allodynia and thermal hyperalgesia in a rat BCP model.